Effects of Caffeine on Metabolism and Mitochondria Biogenesis in Rhabdomyosarcoma Cells Compared with 2,4-Dinitrophenol - Roger A. Vaughan; Randi Garcia-Smith; Marco Bisoffi; Kristina A. Trujillo; Carole A. Conn (Nutrition and Metabolic Insights, 2012)
Purpose This work investigated if treatment with caffeine or 2,4-dinitrophenol (DNP) induce expression of peroxisome proliferator-activated receptor coactivator 1 alpha (PGC-1α) and increase both mitochondrial biosynthesis and metabolism in skeletal muscle. Methods Human rhabdomyosarcoma cells were treated with either ethanol control (0.1% final concentration) caffeine, or DNP at 250 or 500 μM for 16 or 24 hours. PGC-1α RNA levels were determined using quantitative reverse transcriptase polymerase chain reaction (qRT-PCR). PGC-1α protein and mitochondrial content was determined using flow cytometry and immunohistochemistry. Metabolism was determined by quantification of extracellular acidification rate and oxygen consumption rate. Results Treatment with either caffeine or DNP induced PGC-1α RNA and protein as well as mitochondrial content compared with control. Treatment with caffeine and DNP also significantly increased oxidative metabolism and total metabolic rate compared with control. Caffeine similarly increased metabolism and mitochondrial content compared with DNP. Conclusion This work identified that both caffeine and DNP significantly induce PGC-1α, and increase both metabolism and mitochondrial content in skeletal muscle.